APLIKASI KAMUS ISTILAH AKUNTANSI MENGGUNAKAN METODE KNUTH MORRIS PRATT - Eva Darnila (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2015)
The dictionary accounting terms is very benefit the accountants and the parties are engaged in economic, because it can it easier for accountants in searching vocabulary eliminating the need using the general dictionaries. Therefore, it takes a dictionaries the term accounting application integrated with mobile tools will greatly simplify the user in searching meaning of the word of a term in the field of accounting. The process of finding the term application using the Knuth morris pratt the also a method of string matching. Knuth Morris pratt method using the shift characters based on because Knuth Morris pratt method information obtained before the process (pre-process). Knuth method morris pratt do a considerable shift characters using the function limitation rules (border function).